Evaluation of the Level of Smart City Construction Based on Guangfo-Shenzhen-Dongguan in the Context of Guangdong-Hong Kong Macao Greater Bay Area - Zhang, Manting; Wang, Rudan; Xie, Zongyi; He, Haoyu; Li, Shumin; Cen, Yilin; Wu, Haichao; Chu, Chien Chi (Advances in Social Sciences Research Journal, 2022)
The Guangdong Hong Kong-Macao Greater Bay Area is one of the most open and economically dynamic regions in China. The construction of a new type of smart bay area is an important part of the Guangdong-Hong Kong-Macao Greater Bay Area strategy, and the construction of a smart bay area needs to be closely integrated with international standards and focus on building a smart digital centre in the Greater Bay Area. This study focuses on the development needs, future development trends and construction strategies of smart cities in four city clusters in the Guangdong-Hong Kong-Macao Greater Bay Area from four development perspectives: smart water conservancy, smart cultural tourism, smart transportation and smart healthcare, using data related to the development of smart cities in Guangzhou-Foshan-Shenzhen-Dongguan in recent years, the entropy weighting method is used to determine the weights of 40 indicators, and the TOPSIS evaluation model is applied to evaluate the level of smart city construction in each city. The evaluation of the level of smart city construction in each city was carried out by using the TOPSIS evaluation model, and it was concluded that there were large differences among the cities, and there was a need for city-specific policies and reasonable improvements. The evaluation of the level of smart city development in each city was carried out using the TOPSIS evaluation model.